2019
DOI: 10.3389/fncel.2019.00309
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s Disease as a Membrane Disorder: Spatial Cross-Talk Among Beta-Amyloid Peptides, Nicotinic Acetylcholine Receptors and Lipid Rafts

Abstract: Biological membranes show lateral and transverse asymmetric lipid distribution. Cholesterol (Chol) localizes in both hemilayers, but in the external one it is mostly condensed in lipid-ordered microdomains (raft domains), together with saturated phosphatidyl lipids and sphingolipids (including sphingomyelin and glycosphingolipids). Membrane asymmetries induce special membrane biophysical properties and behave as signals for several physiological and/or pathological processes. Alzheimer’s disease (AD) is associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
107
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(111 citation statements)
references
References 459 publications
(515 reference statements)
3
107
1
Order By: Relevance
“…Later, it was shown that α4β2, α4α5β2, and α2αβ nAChRs can also interact with APP and its Aβ peptides [ 61 , 62 ]. In contrast to our data, however, the affinity of Aβ 1-42 to α7 nAChRs in the brain is in the low picomolar range [ 51 , 59 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Later, it was shown that α4β2, α4α5β2, and α2αβ nAChRs can also interact with APP and its Aβ peptides [ 61 , 62 ]. In contrast to our data, however, the affinity of Aβ 1-42 to α7 nAChRs in the brain is in the low picomolar range [ 51 , 59 ].…”
Section: Discussioncontrasting
confidence: 99%
“…APP and its Aβ peptides as well as nAChRs are evolutionary highly conserved and evolved long before the emergence of a nervous system [ 48 , 49 , 50 , 51 ], suggesting that their original functions need to be sought in more primitive and ubiquitous systems, such as innate immunity. Most research has investigated the pathophysiological effects of the interaction of Aβ with α7 nAChRs with a special focus on the etiology of AD [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the plasma membrane cell projection morphogenesis (p<3.98e-17) was significantly enriched. Biologically, this presents remarkable implications for the communication between cell types in the process of amyloid plaque formation [67]. The primary elements of SCZ include changes in cell shape and type rather than strict degradation, as demonstrated in AD-based enrichment.…”
Section: Revealing Disease Related Functions Involving Multiple Cell-mentioning
confidence: 99%
“…Longitudinal and autopsy studies suggest an important contribution of vascular mechanisms (small vessel disease) to cognitive decline in AD associated with type 2 diabetes mellitus [ 60 ]. Hyperglycemia induces vascular permeability by upregulating hypoxia inducible factor-1α (HIF-1α), which subsequently activates vascular endothelial growth factor (VEGF) [ 64 ]. Hyperglycemia also amplifies inflammatory and oxidative processes by contributing to the production of advanced glycation end-products (AGEs) through nonenzymatic glycation and oxidation of lipids, long-lived proteins, and nucleic acids.…”
Section: The Mechanism Underlying Ad Developmentmentioning
confidence: 99%